The construction of opposition relations in high-, middle-, and low-rated postgraduate ESL Chinese students' essays. Issue 34 (July 2018) - Kuzborska, Irena; Soden, Bill
Abstract: The construction of opposition relations is highly expected in writing at higher-university levels. Through specific discourse markers, writers signal these relations to demonstrate precision and awareness of complexity of others' views and to evaluate those views critically. However, despite the high value of opposition relations in advanced academic writing, little is known about students' construction of these relations. To contribute to this knowledge, this study built a corpus of argumentative essays written by native speakers of Chinese as part of their master's course assignments and compared the form and function of opposition relations in low-, middle-, and high-scored student writing. The quantitative analysis showed that the relationship between the frequency of opposition markers and writing score was not significant. However, considerable differences were found between the function and writing score when analysing the results qualitatively. High-scoring students used substantially more concessive and contrast expressions than middle- and low-scoring students. Suggestions for the teaching of opposition relations are discussed. Highlights: The construction of opposition relations at a postgraduate level was examined. The constructions were compared between high-, middle- and low-scoring L2 student writers. There was no relationship between the frequency of opposition markers and writing score. Considerable differences were found between the function and writing score when analysing the results qualitatively. Reasons for the difference in the construction of opposition relations are discussed.